Peripartum cardiomyopathy: a case report - Ferreira,Carla (2014)
The peripartum cardiomyopathy is a rare form of heart disease, defined as the development of maternal congestive heart failure, in the last month of pregnancy or within five months after delivery, with documented left ventricular systolic dysfunction, in the absence of a demonstrable cause in a previously healthy woman. Mortality rates could reach 50%. The authors report a case of 36-year-old woman, gravida IV para IV, obese and smoker, with the diagnosis of peripartum cardiomyopathy established based on clinical status after delivery. Although heart failure treatment optimization was performed with significant clinical improvement, normalization of left ventricle systolic function did not occur at one-year follow-up, establishing the diagnosis of peripartum cardiomyopathy without left ventricular systolic function recovery.